TI_GERICHTE 52.2022.137 vom 23. März 2022 , Revoca della licenza di condurre a tempo indeterminato. Riammissione alla guida - TI Tribunale d'appello (2022)
Revoca della licenza di condurre a tempo indeterminato. Riammissione alla guida